Herpetofauna Diversity and Conservation Value in The Mountain Ecosystems of Gunung Sigogor and Gunung Picis Nature Reserve, East Java, Indonesia - Muammar Kadafi, Ahmad; Fatiqin, Awalul; Priambodo, Bagus; Firmansyah, Richo; Dwi Nur Aji, Fajar; Wahyu Widodo, Tri; Gunawan; Permana, Danafia; Yanuar Adiba, Faisal; Ristanto, Yuri (Biotropika: Journal of Tropical Biology, 2024)
Gunung Picis and Gunung Sigogor nature reserves, located in the Wilis mountain range of East Java, were established in 1924 and 1936, respectively. These areas are critical for biodiversity preservation as mandated by Indonesia's Law No. 5 of 1990 on Conservation of Biological Resources and Ecosystems. Despite previous surveys documenting various mammals, birds, reptiles, and amphibians data remain limited. Herpetofauna, particularly amphibians, are vital bio-indicators due to their sensitivity to environmental changes, but they face significant threats from habitat loss and exploitation. This study, conducted in November 2020 using Visual Encounter Surveys and opportunistic searches, aimed to catalog herpetofauna diversity in these reserves. The survey identified 29 herpetofauna species, with Nyctixalus margaritifer rediscovered at a new site. Most species were classified as Least Concern (LC), except for the Gonocephalus kuhlii (Vulnerable/VU), indicating potential habitat threats. Analysis of species distribution highlighted "Wates stream" as the most diverse habitat. These findings provide a critical foundation for future conservation efforts, emphasizing the need for targeted strategies to protect amphibian and reptile species in Gunung Picis and Gunung Sigogor nature reserve.